Bismuth doping effect on crystal structure and photodegradation activity of Bi–TiO2 nanoparticles. (17th January 2017) - Wu, Ming-Chung; Chang, Yin-Hsuan; Lin, Ting-Han
Abstract: The bismuth precursor is adopted as dopant to synthesize bismuth doped titanium dioxide nanoparticles (Bi–TiO2 NPs) with sol–gel method following by the thermal annealing treatment. We systematically developed a series of Bi–TiO2 NPs at several calcination temperatures and discovered the corresponding crystal structure by varying the bismuth doping concentration. At a certain 650 °C calcination temperature, the crystal structure of bismuth titanate (Bi2 Ti2 O7 ) is formed when the bismuth doping concentration is as high as 10.0 mol %. The photocatalytic activity of Bi–TiO2 NPs is increased by varying the doping concentration at the particular calcination temperature. By the definition X-ray diffraction (XRD) structural identification, a phase diagram of Bi–TiO2 NPs in doping concentration versus calcination temperature is provided. It can be useful for further study in the crystal structure engineering and the development of photocatalyst.